Characterization of pore systems in carbonates using 3D X-Ray computed tomography - Ben-Awuah, Joel; Andriamihaja, S.; Padmanabhan, E. (Slovnaft VÚRUP, 2016)
It is well-known that prediction of petrophysical parameters which is closely linked to pore system complexities is always challenging especially for carbonate rock study. This paper describes and characterizes the pore systems within a carbonate rock, using X- Ray computed tomography imaging. After processing and analyzing series of digital thin sections, pore space is differentiated from matrix and eventually from grains. Pore space parameters such as pore type, connectivity, size, and porosity were extracted and described. The analysis of pore connectivity is more reliable in 3D. The pore type evaluation in 2D points out that the observed pores are moldic, separate – vug while in 3D, some are solution - enlarged as touching –vug pores. The sample is dominated by touching – vug pores by taking into account the pore volume and the connectivity analysis in 3D view. The pore shapes appear irregular and are developed randomly. The shape of the pore varies significantly between intervals of 440μm. The pore size variation differs between each pore. The use of 3D pore model analysis is carried out to complement routine petrographic technique is complementary in order to enhance the classification and the characterization of pore systems in carbonate.